Correlations among the nursing work environment, traumatic stress, and professional quality of life in Chinese midwives: A cross-sectional study - Xiaofei Zhang; Bing Lun; Haojie Ge; Lixia Qu (PLoS ONE, 2025)
Background Midwives work in a high-stress, high-risk, and high-intensity delivery room environment, which exposes them to significant emotional challenges. Understanding the factors influencing midwives’ professional quality of life (ProQoL) is crucial for maintaining their well-being. Although the nursing work environment plays a significant role in ProQoL, a gap in understanding how the nursing work environment and traumatic stress affect midwives’ ProQoL remains, especially in Chinese midwives. Aim The purpose of this study was to identify how the nursing work environment and traumatic stress are related to ProQoL in Chinese midwives. Methods An online questionnaire was administered to 232 midwives working in the delivery room of 59 hospitals in Henan Province, China. The participants were selected via a convenience sampling approach between November and December 2023. The data collection tools used were the Demographic and professional characteristics Questionnaire, Traumatic Stress Scale for Midwives (TSSM) (consisting of frequency and impact), Nursing Work Environment Scale (NWES), and ProQoL (consisting compassion satisfaction, burnout, and secondary traumatic stress). The data were analyzed via the Mann-Whitney U test, the Kruskal-Wallis H test, Spearman’s correlation, and multiple linear regression. Results The study revealed that midwives reported moderate levels of compassion satisfaction (35.18 ± 7.703) and burnout (25.33 ± 4.334), alongside a low level of secondary traumatic stress (21.50 ± 5.464). Results showed that the nursing work environment was positively correlated with compassion satisfaction (r = 0.610) and negatively correlated with burnout (r = −0.390) and secondary traumatic stress (r = −0.296). Midwives’ scores on the frequency and impact of traumatic stress were positively related to burnout (r = 0.254, r = 0.452) and secondary traumatic stress (r = 0.281, r = 0.380) but negatively related to compassion satisfaction (r = −0.145, r = −0.383). Multiple regression analysis results revealed that the nursing work environment, the impact of traumatic stress, major shifts, health condition and the frequency of traumatic stress predicted compassion satisfaction. The impact of traumatic stress, health condition, and the nursing work environment predicted burnout. The impact of traumatic stress, the nursing work environment and frequency of night shifts per month predicted secondary traumatic stress. Conclusions The associations we identified among the nursing work environment, traumatic stress, and ProQoL suggest the potential importance of implementing a supportive nursing work environment and developing strategies such as trauma-informed care education and trauma management for midwives. These strategies are vital in improving midwives’ ProQoL, thereby promoting their health and well-being.